Effect Of Cycleime On Inventory: A Case Study Of Automobile Manufacturing Industry - Kumar, Raman; Chohan, Jasgurpreet Singh; Singh, Sandeep; Verma, Chandershekhar (The journal of contemporary issues in business and government, 2021)
In today competitive era, organizations are focusing to reduce the overworking and optimize their process activities. The planning of inventory is a challenge task for any manufacturing industry. In present work, the effect of reduction in cycle time on the inventory has been investigated in the automobile manufacturing industry. A comparison analysis is performed which the reduction in inventory cost of raw material and bought out parts. The average of inventory cost is calculated after and before the reduction of cycle time. The micro level analysis is performed on customer plan to breakdown the requirement on day basis. A case study is demonstrated to validate the findings of present work.